2017
DOI: 10.1016/j.joa.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Importance of exercise testing shortly after subcutaneous implantable cardioverter‐defibrillator implantation in patients with Brugada syndrome – The first case of associated inappropriate shock in Japan

Abstract: We report the case of a 51-year-old patient with Brugada syndrome (BrS) who experienced inappropriate shock due to T-wave oversensing (TWOS) during exercise when the optimal sensing vector was selected based on the automatic analysis by a subcutaneous implantable cardioverter-defibrillator (S-ICD). After selecting another vector during exercise testing, TWOS did not re-occur. Selection of appropriate sensing vector based on analyses under various conditions, including during exercise after S-ICD implantation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Remarkably, our study showed that patients with IS were significantly younger both at diagnosis and at S‐ICD implantation. Younger individuals are more prone to engage in intense physical activities; hence, they develop exercise‐related IS due to electric noise (myopotentials) or TWOS, 7–10 owing to the dynamic behavior of R‐ and T‐waves during exercise. In a study by Kooiman et al, 10 16% patients implanted with an S‐ICD experienced IS, with 72% of them secondary to TWOS at exercise during a median follow‐up of 21 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, our study showed that patients with IS were significantly younger both at diagnosis and at S‐ICD implantation. Younger individuals are more prone to engage in intense physical activities; hence, they develop exercise‐related IS due to electric noise (myopotentials) or TWOS, 7–10 owing to the dynamic behavior of R‐ and T‐waves during exercise. In a study by Kooiman et al, 10 16% patients implanted with an S‐ICD experienced IS, with 72% of them secondary to TWOS at exercise during a median follow‐up of 21 months.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest the potential benefit of an adequate screening process to select suitable candidates for S‐ICD among BrS patients, especially in those diagnosed at a younger age. Besides the classical requirements, the new proposed criteria may include screening patients during or immediately after an exercise test 7,17,18 and drug challenge, 19 as well as using higher QRS voltage and DASS values and requiring more than one vector passed. The application of these new, stricter criteria plus other strategies, such us pharmacological treatment to reduce heart rate during exercise or advising the patient to avoid certain activities may result in a reduction of this frequent complication, minimizing the need for more aggressive solutions (e.g., repositioning of the electrode and/or the device, replacing the device with a TV‐ICD), or choosing a transvenous device in the first place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 However, contemporary data including new generation S-ICDs, adequate screening, and programming are scarce; indeed some data indicate that the contemporary rates of inadequate therapies in this context may be lower than previously reported. [37][38][39] This notwithstanding, especially patients with Brugada syndrome pose a challenge for current S-ICD systems; diligent screening, implantation, and follow-up are required to reduce the inherently elevated risk of inappropriate shocks in these individuals. 30 Available data from UNTOUCHED also indicate that expert programming and optimal implantation techniques are crucial in order to achieve this level.…”
Section: Safety and Efficacy Of The S-icd-the Prospective Multicentermentioning
confidence: 99%